Making Multicandidate Elections More Democratic - Merrill, Samuel, 1939- (Book collections on Project MUSE., 1988)
This book addresses a significant area of applied social-choice theory--the evaluation of voting procedures designed to select a single winner from a field of three or more candidates. Such procedures can differ strikingly in the election outcomes they produce, the opportunities for manipulation that they create, and the nature of the candidates--centrist or extremist--whom they advantage. The author uses computer simulations based on models of voting behavior and reconstructions of historical elections to assess the likelihood that each multicandidate voting system meets political objectives. Alternative procedures abound: the single-vote plurality method, ubiquitous in the United States, Canada, and Britain; runoff, used in certain primaries; the Borda count, based on rank scores submitted by each voter; approval voting, which permits each voter to support several candidates equally; and the Hare system of successive eliminations, to name a few. This work concludes that single-vote plurality is most often at odds with the majoritarian principle of Condorcet. Those methods most likely to choose the Condorcet candidate under sincere voting are generally the most vulnerable to manipulation. Approval voting and the Hare and runoff methods emerge from the analyses as the most reliable. Originally published in 1988. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.